Trillion game. Volume 1 - Inagaki, Riichiro (VIZ Media, [2024]-, 2024)
"A charming sweet-talker and a timid computer programmer team up with hopes of making a trillion dollars and getting everything they've ever wanted in this world! Self-proclaimed "world's greediest man" Haru and timid computer whiz Gaku set out to make a trillion dollars. They start the company Trillion Game to accomplish this task and hope to iron out the details as they go. With charm, technical skills, and no business plan, can these unlikely friends reach their lofty goal? After Haru and Gaku become the first Japanese people in the 21st century to be listed among the world's top-ten billionaires, Gaku reflects on when he and Haru met and the events that led to the founding of their company. What started as a middle school acquaintanceship builds to a fruitful and unorthodox partnership as the two progress on their ruthless path to success." --